Hydrocellular Foam Dressing Promotes Wound Healing along with Increases in Hyaluronan Synthase 3 and PPARα Gene Expression in Epidermis - Yamane, Takumi (Public Library of Science, 2013)
BACKGROUND: Hydrocellular foam dressing, modern wound dressing, induces moist wound environment and promotes wound healing: however, the regulatory mechanisms responsible for these effects are poorly understood. This study was aimed to reveal the effect of hydrocellular foam dressing on hyaluronan, which has been shown to have positive effects on wound healing, and examined its regulatory mechanisms in rat skin. METHODOLOGY/PRINCIPAL FINDINGS: We created two full-thickness wounds on the dorsolateral skin of rats. Each wound was covered with either a hydrocellular foam dressing or a film dressing and hyaluronan levels in the periwound skin was measured. We also investigated the mechanism by which the hydrocellular foam dressing regulates hyaluronan production by measuring the gene expression of hyaluronan synthase 3 (Has3), peroxisome proliferator-activated receptor α (PPARα), and CD44. Hydrocellular foam dressing promoted wound healing and upregulated hyaluronan synthesis, along with an increase in the mRNA levels of Has3, which plays a primary role in hyaluronan synthesis in epidermis. In addition, hydrocellular foam dressing enhanced the mRNA levels of PPARα, which upregulates Has3 gene expression, and the major hyaluronan receptor CD44. CONCLUSIONS/SIGNIFICANCE: These findings suggests that hydrocellular foam dressing may be beneficial for wound healing along with increases in hyaluronan synthase 3 and PPARα gene expression in epidermis. We believe that the present study would contribute to the elucidation of the mechanisms underlying the effects of hydrocellular foam dressing-induced moist environment on wound healing and practice evidence-based wound care.